Access and utilization of maternal healthcare in a rural district in the forest belt of Ghana - Gladys Buruwaa Nuamah; Peter Agyei-Baffour; Kofi Akohene Mensah; Daniel Boateng; Dan Yedu Quansah; Dominic Dobin; Kwasi Addai-Donkor (BMC, 2019)
Abstract Background Poor maternal health delivery in developing countries results in more than half a million maternal deaths during pregnancy, childbirth or within a few weeks of delivery. This is partly due to unavailability and low utilization of maternal healthcare services in limited-resource settings. The aim of this study was to investigate the access and utilization of maternal healthcare in Amansie-West district in the Ashanti Region of Ghana. Methods An analytical cross-sectional study, involving 720 pregnant women systematically sampled from antenatal clinics in five sub-districts was conducted from February to May 2015 in the Amansie-West district. Data on participants' socio-economic characteristics, knowledge level and access and utilization of maternal health care services were collected with a structured questionnaire. Odds ratios were estimated to describe the association between explanatory variables and maternal healthcare using generalized estimating equations (GEE). Results 68.5, 83.6 and 33.6% of the women had > 3 antenatal care visits, utilized skilled delivery and postnatal care services respectively. The mothers' knowledge level of pregnancy emergencies and newborn danger signs was low. Socio-economic characteristics and healthcare access influenced the utilization of maternal healthcare. Compared to the lowest wealth quintile, being in the highest wealth quintile was associated with higher odds of receiving postnatal care (adjusted odds ratio [aOR]; 95%CI: 2.84; 1.63, 4.94). Use of health facility as a main source of healthcare was also associated with higher odds of antenatal care and skilled delivery. Conclusion This study demonstrates suboptimal access and utilization of maternal healthcare in rural districts of Ghana, which are influenced by socio-economic characteristics of pregnant mothers. This suggests the need for tailored intervention to improve maternal healthcare utilization for mothers in this and other similar settings.